2018
DOI: 10.1007/s11356-018-3076-x
|View full text |Cite
|
Sign up to set email alerts
|

Rice single cropping or ratooning agro-system: which one is more environment-friendly?

Abstract: Sustainable development of food production depends on damping the environmental impacts of agricultural production. The aim of this study was to investigate the environmental performance of rice production in single crop and ratooning (main rice + ratoon crop) agro-systems through life cycle assessment (LCA) methodology in Guilan province, Northern Iran, in 2015. The flooding irrigation regime was the dominant irrigation method for single cropping system and main crop rising in ratooning agro-system. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…This result is slightly lower than the measurement reported by Deng et al (2019), in which N 2 O emissions from the RR season varied from 1.61 to 2.34 kg ha −1 . Fortunately, Firouzi, Nikkhah, and Aminpanah (2018) found that N 2 O emission of the rice ratooning system (1.96 kg 100 kg −1 protein) was less than the corresponding rate in the rice single cropping system (2.88 kg 100 kg −1 protein), which is beneficial to the cultivation and popularization of the ratoon cropping system. These different research results show that further research is needed in the future to clarify the extent of N 2 O emissions from ratoon paddy fields.…”
Section: N 2 O Emissionsmentioning
confidence: 96%
“…This result is slightly lower than the measurement reported by Deng et al (2019), in which N 2 O emissions from the RR season varied from 1.61 to 2.34 kg ha −1 . Fortunately, Firouzi, Nikkhah, and Aminpanah (2018) found that N 2 O emission of the rice ratooning system (1.96 kg 100 kg −1 protein) was less than the corresponding rate in the rice single cropping system (2.88 kg 100 kg −1 protein), which is beneficial to the cultivation and popularization of the ratoon cropping system. These different research results show that further research is needed in the future to clarify the extent of N 2 O emissions from ratoon paddy fields.…”
Section: N 2 O Emissionsmentioning
confidence: 96%
“…Compared to the second seasonal rice cultivation, ratooning rice may significantly decrease the production costs by reducing the input of labor force, fertilizer, pesticides and herbicides [42]. Furthermore, ratooning rice results in better grain quality and less field pollution [42, 43]. Thus the research of ratooning rice is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…There are also some other ways for moving toward a sustainable rice production system. For instance, a study showed rice ratooning is more eco-efficient than the single cropping system (Firouzi et al, 2018). Khoshnevisan et al (2021) indicated that 355% reduction in global warming impact could be achieved under optimal rice-crab co-culture system compared to rice mono-culture.…”
Section: Cdp and Ri Indices In The Proposed Scenariomentioning
confidence: 99%